Evolutionary and Antigenic Profiling of the Tendentious D614G Mutation of SARS-CoV-2 in Gujarat, India - Jay Nimavat (Frontiers Media S.A., 2021)
Humankind has suffered many pandemics in history including measles, SARS, MERS, Ebola, and recently the novel Coronavirus disease caused by SARS-CoV-2. As of September 2021, it has affected over 200 million people and caused over 4 million deaths. India is the second most affected country in the world. Up to this date, more than 38 Lakh viral genomes have been submitted to public repositories like GISAID and NCBI to analyze the virus phylogeny and mutations. Here, we analyzed 2349 genome sequences of SARS-CoV-2 submitted in GISAID by a single institute pertaining to infections from the Gujarat state to know their variants and phylogenetic distributions with a major focus on the spike protein. More than 93% of the genomes had one or more mutations in the spike glycoprotein. The D614G variant in spike protein is reported to have a very high frequency of >95% globally followed by the L452R and P681R, thus getting significant attention. The antigenic propensity of a small peptide of 29 residues from 597 to 625 of the spike protein variants having D614 and G614 showed that G614 has a little higher antigenic propensity. Thus, the D614G is the cause for higher viral antigenicity, however, it has not been reported to be effective to be causing more deaths.